The relationship between work-family conflict, workload, and employee performance of female nurses: The moderating role of job satisfaction - Diandita Syurya Mitra; Herri Herri; Donard Games (Journal of Enterprise and Development (JED), 2023)
Purpose — This study seeks to explore the relationship between work-family conflict, workload, and employee performance, with a specific focus on the moderating role of job satisfaction.Method — The study was carried out at dr. Rasidin Padang Hospital and utilized both descriptive statistical analysis and inferential analysis with SmartPLS 4.0 as the analytical tools. The research involved a sample of 94 participants.Result — The findings indicated that nurse performance is influenced by work-family conflict, workload, and job satisfaction. Additionally, job satisfaction was found to moderate the associations between work-family conflict and nurse performance, as well as between workload and nurse performance.Contribution — This study contributes to the academic literature by incorporating job satisfaction variables to assess nurse performance satisfaction, utilizing a different research location and software (SmartPLS) compared to previous studies, and uniquely focusing on nurses' workload challenges related to working time and limited days off.